Dampak Rendahnya Sikap/Perilaku Harmonis, Adaptif dan Kolaboratif terhadap Kerja Berkelanjutan Pegawai Publik - Ilham Ilham (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The impact of low levels of harmonious, adaptive and collaborative attitudes and behavior on the sustainability of public employees' work. Sustainable work is a necessity for public employees to achieve organizational goals and provide optimal public services. However, low attitudes and behavior can hamper productivity and work efficiency. A harmonious attitude reflects the ability to work well with colleagues, adaptive behavior means being able to adapt to changes in the work environment, and a collaborative attitude means being able to work together with other people to achieve common goals. Harmonious, adaptive and collaborative attitudes are very important, these attitudes in the context of public employees. Adaptive and collaborative attitudes are fundamental pillars in achieving success for public employees in providing services to the community. In the rapidly changing era of globalization, civil servants need to have adaptive abilities to remain productive and provide the best service. The low level of harmonious, adaptive and collaborative attitudes can be caused by a work environment that is not conducive and a lack of adequate training and development. The causes of low levels of harmonious, adaptive and collaborative attitudes and the importance of condescending support in developing these attitudes. By understanding and overcoming these obstacles, public employees can work sustainably, achieve organizational goals, and provide optimal public services.